2013
DOI: 10.1002/hup.2286
|View full text |Cite
|
Sign up to set email alerts
|

Yokukansan in the treatment of behavioral and psychological symptoms of dementia: a systematic review and meta‐analysis of randomized controlled trials

Abstract: Our results suggest that Yokukansan has a beneficial effect on NPI and on ADL scores and that Yokukansan seems to be a well-tolerated treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 18 publications
3
80
3
1
Order By: Relevance
“…YKS is another Kampo formula for which clinical evidence including meta-analysis of its beneficial effects on dementia patients has been accumulated (13). This formula consists of 7 different crude drugs (Table 1).…”
Section: Yksmentioning
confidence: 99%
“…YKS is another Kampo formula for which clinical evidence including meta-analysis of its beneficial effects on dementia patients has been accumulated (13). This formula consists of 7 different crude drugs (Table 1).…”
Section: Yksmentioning
confidence: 99%
“…Thus, the combination of L-DOPA and YKS may be useful for reducing the amount of L-DOPA administered to PD patients; however, further studies are needed. In addition, YKS improved BPSD such as hallucination, agitation, aggressiveness, and anxiety in patients with AD, [1][2][3] DLB, 4,5) PD, or PDD. 6,7) Reduced dopaminergic activity in the striatum and PFC in 6-OHDA-lesioned rats caused anxiogenic responses in the elevated plus-maze test, 49) whereas decreased DA levels in the medial PFC increased anxiety induced by social defeat stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been approved by the Japanese Ministry of Health, Labour and Welfare as a treatment for neurosis, insomnia, and irritability in children. Recently, YKS was reported to reduce the behavioral and psychological symptoms of dementia (BPSD), including agitation, aggressiveness, and hallucinations, not only in patients with Alzheimer's disease (AD) [1][2][3] but also in those with dementia with Lewy bodies (DLB), 4,5) Parkinson's disease (PD), or PD with dementia (PDD), 6,7) which are characterized by progressive dopamine (DA) neuronal loss. These clinical findings suggested that YKS acts on the DA nerve system, but it does not show the extrapyramidal side effects of the typical or atypical antipsychotic drugs used in the treatment of BPSD, which have a DA D 2 receptor antagonistic effect.…”
mentioning
confidence: 99%
“…On the other hand, YKS is prescribed for neurosis, insomnia, and irritability in frailty. Many clinical trials have shown that YKS improved the behavioral and psychological symptoms of dementia, such as hallucination, delusion, agitation, and aggression (Iwasaki et al 2005, Mizukami et al 2009, Matsuda et al 2013, Monji et al 2009, Okahara et al 2010. Subsequently, a meta-analysis was performed to examine the effect of YKS on these symptoms (Matsuda et al 2013).…”
Section: Discussionmentioning
confidence: 99%